Implication of strategic management on business performance / Mohd Safiz Yusoff - Yusoff, Mohd Safiz (Faculty of Business and Management, 2015)
This paper focus on strategic management implementation among in area of Kluang. The aim is to determine the strategic management that affects business performance the most. It is also to assess the relationship between strategic management implementation and performance by SME’s in Kluang. The empirical data come from 62 respondents whom are owner of respective SME in the stated region. The data were analyzed using four analysis methods in interpreting the data collected, namely reliability test to study the consistency and reliability of data, frequency test to determine the respondent profiler, correlation analysis and regression analysis to discover the relation between variables. Based on the final result, the reliability test is marked as good at 0.758. The result showed that the respondent seen strategic management could only moderately help their business to perform, indicating low awareness in the field in descriptive statistics. In correlation analysis, it is revealed that the respondent are not completely practicing and implementing strategic management where strategic formulation is the highest rate practiced, could only obtained low relationship with business performance. Strategy implementation is the least phase practiced by owner of SME in this region while strategic evaluation is practiced at low rate, in achieving better business performance.